Palliative Care for the Elderly with Dementia: Emerging Feelings of the Nurses and Bioethical Reflections (Revista Iberoamericana de Bioética, 2020)
Palliative care in the care of the elderly with dementia is a contemporary strategy. The goal here was to identify the personal and professional characteristics of nurses, learning the nurses’ feelings while caring for elderly with dementia in palliative care. A qualitative study was conducted taking a descriptive-exploratory approach. Data were analyzed using Bardin Content Analysis through recorded interviews. The sample consisted of 14 nurses. The emerging categories were: “Impotence and limitation”, “Sadness for the evolution of the disease” and “Beneficient”. It has been concluded that the feelings of the professional nurses and Bioethics integrate and qualify palliative care.
Keywords: dementia; elderly; nurse; palliative care; emerging feelings